Il lessico italoromanzo del diritto commerciale in prospettiva onomasiologica. Materiali preparatori allo «Historical Lexicon of Commercial Law. Italian, Latin, German» (Carte Romanze, 2025)
The ERC-2020-CoG project MICOLL-Migrating Commercial Law and Language. Rethinking Lex Mercatoria (11th-17th Century) aims to analyse the terminology of European commercial law used during the medieval and early modern periods through the development of an IT tool called Historical Lexicon of Commercial Law. Italian, Latin, German (HLCL). This contribution presents the main features of the resource and provides an onomasiological glossary of commercial law terminology used in the Italo-Romance vernaculars between the 11th and 16th centuries.
Keywords: Commercial law; Italo-Romance vernaculars; Lexicon; Lex mercatoria; Diachronic onomasiology